Spinal epidural Cavernous Hemangioma mimicking Schwannoma: Case report and review of literature - Debanath, Abhinav; Dey, Subir (Nepal Journal of Neuroscience, 2022)
Pure epidural spinal cavernous hemangiomas are encountered rarely in clinical practice. These lesions are more commonly found in the thoracic region and present with features of myelopathy. Presentation is usually insidious due to slow growth of these tumors, however, acute neurological deterioration is possible in cases with intra-lesional hemorrhage. Surgery is the treatment of choice with patients having good outcomes after complete resection. Due to high vascularity there may be excessive blood loss intra-operatively which might limit complete resection. It is for these reasons that these lesions should be considered in the differential diagnosis of spinal epidural lesions. Literature on these lesions reveals that these tumors are pre-operatively misdiagnosed as schwannomas. We report a case of an elderly male who presented with features of myelopathy and an epidural lesion in the thoracic region. A diagnosis of spinal epidural schwannoma with paravertebral extension was made pre-operatively on the basis of imaging characteristics. However, the lesion was found to be highly vascular during surgery and post-resection histopathology revealed a cavernous hemangioma.